Camellia-containing hydrogel alginate fiber mask base cloth and preparation method thereof
By forming an interpenetrating network structure and the water-locking function of mesoporous nano-silica in the seaweed fiber mask base fabric, combined with zinc ion complexation and stress replenishment of camellia oil microcapsules, the problem of insufficient moisturizing and water-locking of the seaweed fiber mask base fabric is solved, achieving a long-lasting moisturizing effect.
Patent Information
- Application Number
- CN202511492939.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-20
- Publication Date
- 2026-01-09
AI Technical Summary
The existing seaweed fiber mask base fabric has insufficient moisturizing and water-locking capabilities, causing the essence to evaporate quickly and making it difficult to meet the needs of long-lasting moisturizing skincare.
The interpenetrating network structure is formed by cross-linking sodium alginate with calcium ions and physical crystallization of polyvinyl alcohol. Combined with the enhancement and water-locking function of mesoporous nano-silica, and through the stress replenishment mechanism of zinc ion-mediated ternary complexation and camellia oil microcapsules, the moisturizing and water-locking performance of the fiber is improved.
It achieves high water content and slow water evaporation in the fibers, forming a synergistic effect of deep moisturizing and surface water locking, significantly improving the long-lasting moisturizing effect of the mask.
Smart Images

Figure CN121287532A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional fiber technology, specifically to a hydrogel seaweed fiber mask base fabric containing camellia flowers and its preparation method. Background Technology
[0002] As the carrier and release medium for the mask essence, the material properties of the mask base fabric directly affect the skincare effect. Currently, the market has formed a pattern of multiple fibers coexisting. Among them, plant fiber base fabrics (such as cotton and bamboo fiber) are widely used due to their advantages of readily available raw materials and low cost, but they have problems such as uneven skin affinity and limited essence carrying capacity; microfiber base fabrics can improve skin adhesion, but due to their dense fiber structure, the essence release rate is too fast, making it difficult to achieve long-lasting nourishment; silk fiber base fabrics are known for their lightness and breathability, but their natural fiber strength is low, making them easy to break during use, and their moisturizing and water-locking ability depends on the essence formula, with weak water retention capacity of their own.
[0003] With the rise of green and natural skincare concepts, seaweed fiber mask base fabrics have gradually become a research hotspot. This type of base fabric uses marine brown algae as raw material, extracting alginic acid and producing it through a spinning process. It possesses significant natural advantages: firstly, it has excellent biocompatibility, low irritation to sensitive skin, and is biodegradable, aligning with environmental trends; secondly, the polysaccharides in seaweed fibers give them a certain degree of moisture absorption, allowing them to hold more mask essence and facilitating the penetration of the essence into the skin's surface through their fiber structure. Therefore, its application prospects in the beauty and skincare field are widely regarded as promising.
[0004] However, existing seaweed fiber mask base fabrics still have key performance shortcomings in practical applications, and their moisturizing and water-locking capabilities need improvement. Due to the large gaps between seaweed fibers and the lack of an effective water-blocking mechanism in their simple fiber structure, the essence contained within the base fabric evaporates quickly during application due to increased facial temperature and ambient air movement. Water is not only a carrier for dissolving and delivering nutrients in the essence, but its continued presence is also fundamental for skin absorption and hydration. Rapid water loss directly reduces the utilization rate of the essence, thereby decreasing the mask's moisturizing and nourishing effects and failing to meet consumers' demands for long-lasting moisturizing skincare. Therefore, it is urgent to improve and optimize the moisturizing performance of seaweed fiber mask base fabrics through technological advancements. Summary of the Invention
[0005] The purpose of this invention is to provide a hydrogel seaweed fiber facial mask base fabric containing camellia flowers and its preparation method, thereby solving the technical problems mentioned in the background section. The seaweed fiber facial mask base fabric prepared by this invention has excellent moisturizing and water-locking effects.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A method for preparing a hydrogel seaweed fiber mask base fabric containing camellia flowers includes the following steps:
[0008] S1. Mix sodium alginate solution with polyvinyl alcohol solution, then add polyethylene glycol and mesoporous nano silica, and after mechanical stirring and vacuum degassing, obtain a uniform spinning solution.
[0009] S2. The spinning solution is extruded into a composite coagulation bath composed of calcium chloride and calcium gluconate through a wet spinning device, and then subjected to ionic cross-linking solidification and stretching. After that, the solution is subjected to freezing and thawing cycle treatment to obtain nascent fibers.
[0010] S3. Prepare a complexing solution containing camellia extract and zinc sulfate heptahydrate, immerse the nascent fibers in the solution and shake to obtain fiber intermediates;
[0011] S4. Using gelatin and gum arabic as wall materials and camellia oil as core material, microcapsules are obtained after curing with a crosslinking agent; the microcapsules are dispersed in an aqueous polyurethane adhesive solution to form a slurry, and the fiber intermediate is immersed in the slurry for padding and heat treatment to obtain hydrogel seaweed fiber containing camellia.
[0012] S5. The hydrogel seaweed fiber containing camellia is opened and combed, and then the fiber is laid into a uniform fiber web by mechanical stacking or air-laid web formation. The fiber web is then subjected to hydroentanglement reinforcement treatment to obtain the hydrogel seaweed fiber mask base fabric containing camellia.
[0013] In this invention, the moisturizing and water-locking properties of the seaweed fiber mask base fabric are improved synergistically from two aspects. Firstly, an interpenetrating dual-network structure is formed through the calcium ion crosslinking of sodium alginate and the freeze-thaw crystallization of polyvinyl alcohol. The sodium alginate ion crosslinking network (first network) provides a rigid three-dimensional skeleton and a large number of hydrophilic groups through an "egg-box model," endowing the fiber with extremely high initial water absorption capacity. Meanwhile, the polyvinyl alcohol physical crystallization network (second network) acts as a dynamic and reversible toughening unit, dispersing and absorbing external stress like a molecular spring, effectively inhibiting the structural damage and disintegration that easily occurs in a single calcium alginate network when it absorbs water and swells. These two networks allow the fiber to swell rapidly upon encountering water while maintaining its mechanical integrity, thus creating a stable, high-water-content hydrogel reservoir. This provides a solid physical basis for long-lasting moisturizing and directly leads to a significant improvement in tensile strength and anti-swelling ability. In this dual-network system, nano-silica plays a dual role as a multifunctional cross-linking point and a moisture regulating valve: First, the numerous silanol groups on its surface can form dense hydrogen bonds with the carboxyl groups of sodium alginate and the hydroxyl groups of polyvinyl alcohol, serving as additional physical cross-linking points, significantly enhancing network density, thereby greatly improving the fiber's breaking strength and wear resistance; Second, these nanoparticles have a huge specific surface area and abundant mesoporous structure, which can adsorb and lock a large number of water molecules through capillary coagulation effect, effectively delaying the free movement and rapid evaporation of water, and reducing the water evaporation rate.
[0014] On the other hand, the stable ternary complex formed by zinc ions, sodium alginate carboxyl groups, and polyphenolic hydroxyl groups in camellia extract firmly anchors small-molecule moisturizing ingredients (such as camellia saponins and tea polyphenols) to the fiber backbone, achieving slow and long-lasting release and extending the moisturizing time. Furthermore, the camellia oil microcapsules encapsulated by the wall material act as an independent stress-replenishing reservoir. They rupture upon contact with the skin via friction or pressure, instantly releasing the oil components. These oils, together with the hydrogel, form a biomimetic sebum film on the skin surface, effectively slowing down transdermal evaporation and thus achieving a moisturizing and water-locking effect.
[0015] Preferably, in step S1, the mass ratio of sodium alginate to polyvinyl alcohol is 10:2 to 4.
[0016] Preferably, the mesoporous nano-silica undergoes a modification treatment, including the following steps:
[0017] S11. Mesoporous nano-silica is dispersed in toluene. Under inert atmosphere and stirring conditions, (3-aminopropyl)triethoxysilane is added to the system, the reaction is heated, the solid product is separated, washed with organic solvent, and dried to obtain aminated silica.
[0018] S12. Aminated silica is dispersed in a mixed solvent consisting of deionized water and anhydrous ethanol, and then sodium chloroacetate is added. Under vigorous stirring, the pH of the reaction system is maintained between 9 and 11 using an alkaline solution. The reaction is heated, the solid product is separated, and after washing and drying, modified mesoporous nano silica is obtained.
[0019] In the technical solution of this invention, the research team discovered that calcium ions have formed a stable "egg-box" cross-linking structure with the guluronic acid units on the sodium alginate chain, occupying most of the high-affinity coordination sites. This means that subsequently introduced zinc ions can only bind to the remaining low-energy-efficiency sites. Simultaneously, the polyvinyl alcohol molecular chains and unmodified nano-silica together form a dense physical network, generating a significant steric hindrance effect. This hinders the diffusion and deep complexation of zinc ions into the fiber interior, ultimately resulting in low zinc ion loading and uneven distribution, severely limiting the synergistic effect of both.
[0020] To further address this technical problem, our team modified mesoporous nano-silica by grafting iminodiacetic acid (IDA) strong metal chelating groups onto its surface. The modified silica transformed from an inert reinforcing filler into a highly efficient zinc ion trap. The IDA ligands on its surface exhibit extremely high specific affinity and chelation selectivity for zinc ions (far exceeding their affinity for calcium ions), enabling it to actively enrich zinc ions from the treatment solution and establish localized high-zinc-ion concentration microregions near the crosslinking points of the polymer network. This not only effectively avoids site competition with calcium ions but also opens up and promotes the transport and complexation pathways of zinc ions within the fibers. This transforms silica from a potential diffusion barrier into a functional component that actively promotes the formation of ternary complexes, thereby significantly improving the loading efficiency and complexation stability of camellia active ingredients.
[0021] Preferably, in step S11, the mass ratio of mesoporous nano-silica to (3-aminopropyl)triethoxysilane is 10:0.5-1.0.
[0022] Preferably, in step S12, the mass ratio of aminated silica to sodium chloroacetate is 10:5 to 8.
[0023] Preferably, in step S2, the mass ratio of calcium chloride to calcium gluconate is 40:1 to 3.
[0024] Preferably, in step S2, the method for preparing the camellia extract includes the following steps:
[0025] S21. Dry and pulverize the camellia flowers into camellia flower powder, mix the camellia flower powder with an ethanol aqueous solution, and extract with ultrasonic assistance under heating conditions to obtain an extract;
[0026] S22. Filter the extract, collect the filtrate, heat and concentrate under reduced pressure to obtain crude camellia extract;
[0027] S23. After dissolving the crude extract of camellia in water, it is purified by passing it through a macroporous adsorption resin column. First, impurities are removed by elution with water, and then elution is carried out with an ethanol aqueous solution. The eluent is collected.
[0028] S24. After concentrating the eluent under reduced pressure under heating conditions, freeze-dry it to obtain camellia extract.
[0029] Preferably, in step S3, the mass ratio of camellia extract to zinc sulfate heptahydrate is 8:3 to 5.
[0030] Preferably, in step S4, the mass ratio of gelatin to gum arabic is 1:0.5 to 1.
[0031] A hydrogel seaweed fiber mask base fabric containing camellia flowers is prepared by the above method.
[0032] Compared with the prior art, the beneficial effects of the present invention are:
[0033] 1. An interpenetrating double network structure is formed by the sodium alginate calcium ion crosslinking network and the polyvinyl alcohol physical crystallization network. Combined with the reinforcement and water-locking function of mesoporous nano silica, a fiber skeleton with excellent mechanical properties, high water content and slow water evaporation is constructed.
[0034] 2. The camellia extract is released slowly and continuously through zinc ion-mediated ternary complexation. At the same time, the camellia oil microcapsules form a biomimetic sebum film on the skin surface through stress replenishment mechanism, resulting in a synergistic effect of deep moisturizing and surface water locking.
[0035] 3. By modifying the surface of mesoporous nano-silica and grafting iminodiacetic acid strong metal chelating groups, it is transformed from an inert filler into a zinc ion trap, which effectively solves the problem of calcium and zinc ion site competition and significantly improves the loading efficiency and complexation stability of active ingredients. Attached Figure Description
[0036] Figure 1 SEM image of the surface of the hydrogel seaweed fiber containing camellia flowers prepared according to the present invention. Detailed Implementation
[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] Example 1
[0039] A method for preparing a hydrogel seaweed fiber facial mask base fabric containing camellia flowers includes the following steps:
[0040] Step 1: 10.0 g of mesoporous nano-silica was dispersed in 200 mL of toluene. Under nitrogen protection and mechanical stirring, 0.9 g of (3-aminopropyl)triethoxysilane was added, and the mixture was heated to 80 °C and refluxed for 6 h. After the reaction was completed, the solid product was separated by vacuum filtration, washed three times with anhydrous ethanol, and dried in a vacuum drying oven at 60 °C for 12 h to obtain aminated silica.
[0041] 10.0 g of aminated silica was dispersed in a mixed solvent consisting of 100 mL of deionized water and 100 mL of anhydrous ethanol. Then, 7.0 g of sodium chloroacetate was added. Under vigorous stirring, the pH of the reaction system was maintained at 10 with 1 M sodium hydroxide solution, and the reaction was carried out in a water bath at 60 °C for 4 h. After the reaction was completed, the solid was collected by suction filtration, washed with deionized water until the filtrate was neutral, and finally dried under vacuum at 60 °C to obtain modified mesoporous nano-silica.
[0042] Weigh 10.0 g of sodium alginate and slowly add it to 90 mL of continuously stirred deionized water. Stir at room temperature for 6 hours until completely dissolved to obtain a sodium alginate solution. Separately weigh 3.5 g of polyvinyl alcohol and add it to 50 mL of 90°C deionized water. Stir vigorously in a 90°C water bath for 3 hours until completely dissolved to obtain a PVA solution, and then cool to 50°C. Mix the two solutions, then add 0.3 g of polyethylene glycol 400 and 0.3 g of modified mesoporous nano-silica. Mechanically stir at 350 rpm for 5 hours in a 50°C water bath. Finally, degas the mixture under a vacuum of -0.095 MPa for 60 minutes to obtain a homogeneous and transparent SA-PVA blend spinning solution.
[0043] Step 2: Dissolve 40.0g of calcium chloride and 2.5g of calcium gluconate in 1L of deionized water, stirring until completely dissolved. Place in a composite coagulation bath, maintaining a constant temperature of 40℃. Load the SA-PVA blend spinning solution into an injection pump, using a spinneret with an inner diameter of 0.12mm, and vertically inject the spinning solution into the coagulation bath at a constant rate of 6mL / h. The nascent fibers remain in the coagulation bath for 90s to solidify, during which time they are drawn through guide rollers at a speed of 3.5 m / min. Remove the solidified fibers, rinse thoroughly with deionized water, and absorb excess surface moisture with filter paper. Then, wrap the fibers in plastic wrap and freeze at -20℃ for 4 hours, followed by thawing at a constant temperature of 25℃ for 2 hours. Repeat this freeze-thaw cycle three times to obtain double-network hydrogel nascent fibers.
[0044] Step 3: Crush 100g of dried camellia flowers and pass them through a 40-mesh sieve. Add the powder to 1.5L of 60% (v / v) ethanol aqueous solution and perform ultrasonic-assisted extraction (ultrasonic power 300W) for 60min at 55℃. Filter the extract through a Buchner funnel, collect the filtrate, and rotary evaporate it under reduced pressure at 50℃ until no alcohol odor remains, obtaining crude camellia flower extract. Dissolve the crude extract in deionized water and load it onto a pretreated AB-8 macroporous adsorption resin column. Elute with water until the eluent is colorless, then elute with 50% (v / v) ethanol aqueous solution, collecting the eluent. Concentrate the eluent under reduced pressure at 50℃ and freeze-dry to obtain a brownish-yellow camellia flower extract.
[0045] Weigh 8.0 g of camellia extract and 4.5 g of zinc sulfate heptahydrate, dissolve them in 188 mL of deionized water, and stir until completely dissolved to obtain a treatment solution. Immerse the nascent double-network hydrogel fibers in this treatment solution at a bath ratio of 1:15, and treat them in a water bath shaker at 70 rpm for 50 min at 45 °C. After treatment, remove the fibers and blot off surface droplets with filter paper to obtain a fiber intermediate loaded with camellia extract.
[0046] Step 4: Dissolve 1.0 g of gelatin in 20 mL of 50°C deionized water to obtain solution A; dissolve 0.9 g of gum arabic in 20 mL of 50°C deionized water to obtain solution B. Mix solution A with 1.0 g of camellia oil and homogenize at 8500 rpm for 3 min to form a primary emulsion. Add solution B to the primary emulsion with slow stirring, mix well, and adjust the pH of the system to 7.5 with 1% NaOH solution. Then, with continuous stirring, slowly lower the pH of the system to 4.2 with 10% acetic acid solution, and then transfer to an ice-water bath to cool to below 10°C. Add 0.1 g of genipin as a crosslinking agent and continue stirring to solidify for 3 h. After the reaction is complete, collect the microcapsules by filtration, wash three times with cold deionized water, and obtain camellia oil microcapsules.
[0047] Camellia oil microcapsules were dispersed in 20g of a 10% aqueous polyurethane (WPU) adhesive solution and ultrasonically dispersed for 2 minutes to form a homogeneous slurry. The fiber intermediate was then impregnated with this slurry, with the roll-off rate controlled at 85%, and then heat-treated in a 75℃ forced-air drying oven for 15 minutes to obtain hydrogel seaweed fibers containing camellia active ingredients.
[0048] Step 5: Open and comb the hydrogel seaweed fibers containing camellia flowers to make them fluffy single fibers. Then, use an air-jet web forming machine to lay the fibers into a surface density of 45 g / m². 2A uniform fiber web is obtained. This fiber web is fed into a hydroentangling reinforcement device, where it is pierced by water flow through three hydroentangling heads under a hydroentangling pressure of 40 bar. Then, it is gently dried in an oven at 65°C for 10 minutes to obtain the mask base fabric.
[0049] Example 2
[0050] A method for preparing a hydrogel seaweed fiber facial mask base fabric containing camellia flowers includes the following steps:
[0051] Step 1: 10.0 g of mesoporous nano-silica was dispersed in 200 mL of toluene. Under nitrogen protection and mechanical stirring, 0.6 g of (3-aminopropyl)triethoxysilane was added, and the mixture was heated to 80 °C and refluxed for 6 h. After the reaction was completed, the solid product was separated by vacuum filtration, washed three times with anhydrous ethanol, and dried in a vacuum drying oven at 60 °C for 12 h to obtain aminated silica.
[0052] 10.0 g of aminated silica was dispersed in a mixed solvent consisting of 100 mL of deionized water and 100 mL of anhydrous ethanol. Then, 6.0 g of sodium chloroacetate was added. Under vigorous stirring, the pH of the reaction system was maintained at 10 with 1 M sodium hydroxide solution, and the reaction was carried out in a water bath at 60 °C for 4 h. After the reaction was completed, the solid was collected by suction filtration, washed with deionized water until the filtrate was neutral, and finally dried under vacuum at 60 °C to obtain modified mesoporous nano-silica.
[0053] Weigh 10.0 g of sodium alginate and slowly add it to 90 mL of continuously stirred deionized water. Stir at room temperature for 6 hours until completely dissolved to obtain a sodium alginate solution. Separately weigh 2.5 g of polyvinyl alcohol and add it to 50 mL of 90°C deionized water. Stir vigorously in a 90°C water bath for 3 hours until completely dissolved to obtain a PVA solution, and then cool to 50°C. Mix the two solutions, then add 0.3 g of polyethylene glycol 400 and 0.3 g of modified mesoporous nano-silica. Mechanically stir at 350 rpm for 5 hours in a 50°C water bath. Finally, degas the mixture under a vacuum of -0.095 MPa for 60 minutes to obtain a homogeneous and transparent SA-PVA blend spinning solution.
[0054] Step 2: Dissolve 40.0g of calcium chloride and 1.5g of calcium gluconate in 1L of deionized water, stirring until completely dissolved. Place the mixture in a coagulation bath, maintaining a constant temperature of 40℃. Load the SA-PVA blend spinning solution into a syringe pump, using a spinneret with an inner diameter of 0.12mm, and vertically inject the spinning solution into the coagulation bath at a constant rate of 6mL / h. The nascent fibers remain in the coagulation bath for 90s to solidify, during which time they are drawn through guide rollers at a speed of 3.5 m / min. Remove the solidified fibers, rinse thoroughly with deionized water, and absorb excess surface moisture with filter paper. Then, wrap the fibers in plastic wrap and freeze at -20℃ for 4 hours, followed by thawing at a constant temperature of 25℃ for 2 hours. Repeat this freeze-thaw cycle three times to obtain double-network hydrogel nascent fibers.
[0055] Step 3: Crush 100g of dried camellia flowers and pass them through a 40-mesh sieve. Add the powder to 1.5L of 60% (v / v) ethanol aqueous solution and perform ultrasonic-assisted extraction (ultrasonic power 300W) for 60min at 55℃. Filter the extract through a Buchner funnel, collect the filtrate, and rotary evaporate it under reduced pressure at 50℃ until no alcohol odor remains, obtaining crude camellia flower extract. Dissolve the crude extract in deionized water and load it onto a pretreated AB-8 macroporous adsorption resin column. Elute with water until the eluent is colorless, then elute with 50% (v / v) ethanol aqueous solution, collecting the eluent. Concentrate the eluent under reduced pressure at 50℃ and freeze-dry to obtain a brownish-yellow camellia flower extract.
[0056] Weigh 8.0 g of camellia extract and 3.5 g of zinc sulfate heptahydrate, dissolve them in 188 mL of deionized water, and stir until completely dissolved to obtain a treatment solution. Immerse the nascent double-network hydrogel fibers in this treatment solution at a bath ratio of 1:15, and treat them in a water bath shaker at 70 rpm for 50 min at 45 °C. After treatment, remove the fibers and blot off surface droplets with filter paper to obtain a fiber intermediate loaded with camellia extract.
[0057] Step 4: Dissolve 1.0 g of gelatin in 20 mL of 50°C deionized water to obtain solution A; dissolve 0.6 g of gum arabic in 20 mL of 50°C deionized water to obtain solution B. Mix solution A with 1.0 g of camellia oil and homogenize at 8500 rpm for 3 min to form a primary emulsion. Add solution B to the primary emulsion with slow stirring, mix well, and adjust the pH of the system to 7.5 with 1% NaOH solution. Then, with continuous stirring, slowly lower the pH of the system to 4.2 with 10% acetic acid solution, then transfer to an ice-water bath to cool to below 10°C, add 0.1 g of genipin as a crosslinking agent, and continue stirring to solidify for 3 h. After the reaction is complete, collect the microcapsules by filtration, wash three times with cold deionized water, and obtain camellia oil microcapsules.
[0058] Camellia oil microcapsules were dispersed in 20g of a 10% aqueous polyurethane (WPU) adhesive solution and ultrasonically dispersed for 2 minutes to form a homogeneous slurry. The fiber intermediate was then impregnated with this slurry, with the roll-off rate controlled at 85%, and then heat-treated in a 75℃ forced-air drying oven for 15 minutes to obtain hydrogel seaweed fibers containing camellia active ingredients.
[0059] Step 5: Open and comb the hydrogel seaweed fibers containing camellia flowers to make them fluffy single fibers. Then, use an air-jet web forming machine to lay the fibers into a surface density of 45 g / m². 2 A uniform fiber web is obtained. This fiber web is fed into a hydroentangling reinforcement device, where it is pierced by water flow through three hydroentangling heads under a hydroentangling pressure of 40 bar. Then, it is gently dried in an oven at 65°C for 10 minutes to obtain the mask base fabric.
[0060] Example 3
[0061] A method for preparing a hydrogel seaweed fiber facial mask base fabric containing camellia flowers includes the following steps:
[0062] Step 1: 10.0 g of mesoporous nano-silica was dispersed in 200 mL of toluene. Under nitrogen protection and mechanical stirring, 0.8 g of (3-aminopropyl)triethoxysilane was added, and the mixture was heated to 80 °C and refluxed for 6 h. After the reaction was completed, the solid product was separated by vacuum filtration, washed three times with anhydrous ethanol, and dried in a vacuum drying oven at 60 °C for 12 h to obtain aminated silica.
[0063] 10.0 g of aminated silica was dispersed in a mixed solvent consisting of 100 mL of deionized water and 100 mL of anhydrous ethanol. Then, 6.5 g of sodium chloroacetate was added. Under vigorous stirring, the pH of the reaction system was maintained at 10 with 1 M sodium hydroxide solution, and the reaction was carried out in a water bath at 60 °C for 4 h. After the reaction was completed, the solid was collected by suction filtration, washed with deionized water until the filtrate was neutral, and finally dried under vacuum at 60 °C to obtain modified mesoporous nano-silica.
[0064] Weigh 10.0 g of sodium alginate and slowly add it to 90 mL of continuously stirred deionized water. Stir at room temperature for 6 hours until completely dissolved to obtain a sodium alginate solution. Separately weigh 3.0 g of polyvinyl alcohol and add it to 50 mL of 90°C deionized water. Stir vigorously in a 90°C water bath for 3 hours until completely dissolved to obtain a PVA solution, and then cool to 50°C. Mix the two solutions, then add 0.3 g of polyethylene glycol 400 and 0.3 g of modified mesoporous nano-silica. Mechanically stir at 350 rpm for 5 hours in a 50°C water bath. Finally, degas the mixture under a vacuum of -0.095 MPa for 60 minutes to obtain a homogeneous and transparent SA-PVA blend spinning solution.
[0065] Step 2: Dissolve 40.0g calcium chloride and 2.0g calcium gluconate in 1L of deionized water, stirring until completely dissolved. Place in a composite coagulation bath, maintaining a constant temperature of 40℃. Load the SA-PVA blend spinning solution into an injection pump, using a spinneret with an inner diameter of 0.12mm, and vertically inject the spinning solution into the coagulation bath at a constant rate of 6mL / h. The nascent fibers remain in the coagulation bath for 90s to solidify, during which time they are drawn through guide rollers at a speed of 3.5 m / min. Remove the solidified fibers, rinse thoroughly with deionized water, and absorb excess surface moisture with filter paper. Then, wrap the fibers in plastic wrap and freeze at -20℃ for 4 hours, followed by thawing at a constant temperature of 25℃ for 2 hours. Repeat this freeze-thaw cycle three times to obtain double-network hydrogel nascent fibers.
[0066] Step 3: Crush 100g of dried camellia flowers and pass them through a 40-mesh sieve. Add the powder to 1.5L of 60% (v / v) ethanol aqueous solution and perform ultrasonic-assisted extraction (ultrasonic power 300W) for 60min at 55℃. Filter the extract through a Buchner funnel, collect the filtrate, and rotary evaporate it under reduced pressure at 50℃ until no alcohol odor remains, obtaining crude camellia flower extract. Dissolve the crude extract in deionized water and load it onto a pretreated AB-8 macroporous adsorption resin column. Elute with water until the eluent is colorless, then elute with 50% (v / v) ethanol aqueous solution, collecting the eluent. Concentrate the eluent under reduced pressure at 50℃ and freeze-dry to obtain a brownish-yellow camellia flower extract.
[0067] Weigh 8.0 g of camellia extract and 4.0 g of zinc sulfate heptahydrate, dissolve them in 188 mL of deionized water, and stir until completely dissolved to obtain a treatment solution. Immerse the nascent double-network hydrogel fibers in this treatment solution at a bath ratio of 1:15, and treat them in a water bath shaker at 70 rpm for 50 min at 45 °C. After treatment, remove the fibers and blot off surface droplets with filter paper to obtain a fiber intermediate loaded with camellia extract.
[0068] Step 4: Dissolve 1.0 g of gelatin in 20 mL of 50°C deionized water to obtain solution A; dissolve 0.8 g of gum arabic in 20 mL of 50°C deionized water to obtain solution B. Mix solution A with 1.0 g of camellia oil and homogenize at 8500 rpm for 3 min to form a primary emulsion. Add solution B to the primary emulsion with slow stirring, mix well, and adjust the pH of the system to 7.5 with 1% NaOH solution. Then, with continuous stirring, slowly lower the pH of the system to 4.2 with 10% acetic acid solution, and then transfer to an ice-water bath to cool to below 10°C. Add 0.1 g of genipin as a crosslinking agent and continue stirring to solidify for 3 h. After the reaction is complete, collect the microcapsules by filtration, wash three times with cold deionized water, and obtain camellia oil microcapsules.
[0069] Camellia oil microcapsules were dispersed in 20g of a 10% aqueous polyurethane (WPU) adhesive solution and ultrasonically dispersed for 2 minutes to form a homogeneous slurry. The fiber intermediate was then impregnated with this slurry, with the roll-off rate controlled at 85%, and then heat-treated in a 75℃ forced-air drying oven for 15 minutes to obtain hydrogel seaweed fibers containing camellia active ingredients.
[0070] Step 5: Open and comb the hydrogel seaweed fibers containing camellia flowers to make them fluffy single fibers. Then, use an air-jet web forming machine to lay the fibers into a surface density of 45 g / m². 2 A uniform fiber web is obtained. This fiber web is fed into a hydroentangling reinforcement device, where it is pierced by water flow through three hydroentangling heads under a hydroentangling pressure of 40 bar. Then, it is gently dried in an oven at 65°C for 10 minutes to obtain the mask base fabric.
[0071] Example 4
[0072] A method for preparing a hydrogel seaweed fiber facial mask base fabric containing camellia flowers includes the following steps:
[0073] Step 1: 10.0 g of mesoporous nano-silica was dispersed in 200 mL of toluene. Under nitrogen protection and mechanical stirring, 1.0 g of (3-aminopropyl)triethoxysilane was added, and the mixture was heated to 80 °C and refluxed for 6 h. After the reaction was completed, the solid product was separated by vacuum filtration, washed three times with anhydrous ethanol, and dried in a vacuum drying oven at 60 °C for 12 h to obtain aminated silica.
[0074] 10.0 g of aminated silica was dispersed in a mixed solvent consisting of 100 mL of deionized water and 100 mL of anhydrous ethanol. Then, 8.0 g of sodium chloroacetate was added. Under vigorous stirring, the pH of the reaction system was maintained at 11 with 1 M sodium hydroxide solution, and the reaction was carried out in a water bath at 60 °C for 4 h. After the reaction was completed, the solid was collected by suction filtration, washed with deionized water until the filtrate was neutral, and finally dried under vacuum at 60 °C to obtain modified mesoporous nano-silica.
[0075] Weigh 10.0 g of sodium alginate and slowly add it to 90 mL of continuously stirred deionized water. Stir at room temperature for 6 hours until completely dissolved to obtain a sodium alginate solution. Separately weigh 4.0 g of polyvinyl alcohol and add it to 50 mL of 90°C deionized water. Stir vigorously in a 90°C water bath for 3 hours until completely dissolved to obtain a PVA solution, and then cool to 50°C. Mix the two solutions, then add 0.3 g of polyethylene glycol 400 and 0.3 g of modified mesoporous nano-silica. Mechanically stir at 350 rpm for 5 hours in a 50°C water bath. Finally, degas the mixture under a vacuum of -0.095 MPa for 60 minutes to obtain a homogeneous and transparent SA-PVA blend spinning solution.
[0076] Step 2: Dissolve 40.0g calcium chloride and 3.0g calcium gluconate in 1L of deionized water, stirring until completely dissolved. Place in a composite coagulation bath, maintaining a constant temperature of 40℃. Load the SA-PVA blend spinning solution into an injection pump, using a spinneret with an inner diameter of 0.12mm, and vertically inject the spinning solution into the coagulation bath at a constant rate of 6mL / h. The nascent fibers remain in the coagulation bath for 90s to solidify, during which time they are drawn through guide rollers at a speed of 3.5 m / min. Remove the solidified fibers, rinse thoroughly with deionized water, and absorb excess surface moisture with filter paper. Then, wrap the fibers in plastic wrap and freeze at -20℃ for 4 hours, followed by thawing at a constant temperature of 25℃ for 2 hours. Repeat this freeze-thaw cycle three times to obtain double-network hydrogel nascent fibers.
[0077] Step 3: Crush 100g of dried camellia flowers and pass them through a 40-mesh sieve. Add the powder to 1.5L of 60% (v / v) ethanol aqueous solution and perform ultrasonic-assisted extraction (ultrasonic power 300W) for 60min at 55℃. Filter the extract through a Buchner funnel, collect the filtrate, and rotary evaporate it under reduced pressure at 50℃ until no alcohol odor remains, obtaining crude camellia flower extract. Dissolve the crude extract in deionized water and load it onto a pretreated AB-8 macroporous adsorption resin column. Elute with water until the eluent is colorless, then elute with 50% (v / v) ethanol aqueous solution, collecting the eluent. Concentrate the eluent under reduced pressure at 50℃ and freeze-dry to obtain a brownish-yellow camellia flower extract.
[0078] Weigh 8.0 g of camellia extract and 5.0 g of zinc sulfate heptahydrate, dissolve them in 188 mL of deionized water, and stir until completely dissolved to obtain a treatment solution. Immerse the nascent double-network hydrogel fibers in this treatment solution at a bath ratio of 1:15, and treat them in a water bath shaker at 70 rpm for 50 min at 45 °C. After treatment, remove the fibers and blot off surface droplets with filter paper to obtain a fiber intermediate loaded with camellia extract.
[0079] Step 4: Dissolve 1.0 g of gelatin in 20 mL of 50°C deionized water to obtain solution A; dissolve 1.0 g of gum arabic in 20 mL of 50°C deionized water to obtain solution B. Mix solution A with 1.0 g of camellia oil and homogenize at 8500 rpm for 3 min to form a primary emulsion. Add solution B to the primary emulsion with slow stirring, mix well, and adjust the pH of the system to 7.5 with 1% NaOH solution. Then, with continuous stirring, slowly lower the pH of the system to 4.2 with 10% acetic acid solution, and then transfer to an ice-water bath to cool to below 10°C. Add 0.1 g of genipin as a crosslinking agent and continue stirring to solidify for 3 h. After the reaction is complete, collect the microcapsules by filtration, wash three times with cold deionized water, and obtain camellia oil microcapsules.
[0080] Camellia oil microcapsules were dispersed in 20g of a 10% aqueous polyurethane (WPU) adhesive solution and ultrasonically dispersed for 2 minutes to form a homogeneous slurry. The fiber intermediate was then impregnated with this slurry, with the roll-off rate controlled at 85%, and then heat-treated in a 75℃ forced-air drying oven for 15 minutes to obtain hydrogel seaweed fibers containing camellia active ingredients.
[0081] Step 5: Open and comb the hydrogel seaweed fibers containing camellia flowers to make them fluffy single fibers. Then, use an air-jet web forming machine to lay the fibers into a surface density of 45 g / m². 2 A uniform fiber web is obtained. This fiber web is fed into a hydroentangling reinforcement device, where it is pierced by water flow through three hydroentangling heads under a hydroentangling pressure of 40 bar. Then, it is gently dried in an oven at 65°C for 10 minutes to obtain the mask base fabric.
[0082] Example 5
[0083] A method for preparing a hydrogel seaweed fiber facial mask base fabric containing camellia flowers includes the following steps:
[0084] Step 1: 10.0 g of mesoporous nano-silica was dispersed in 200 mL of toluene. Under nitrogen protection and mechanical stirring, 0.5 g of (3-aminopropyl)triethoxysilane was added, and the mixture was heated to 80 °C and refluxed for 6 h. After the reaction was completed, the solid product was separated by vacuum filtration, washed three times with anhydrous ethanol, and dried in a vacuum drying oven at 60 °C for 12 h to obtain aminated silica.
[0085] 10.0 g of aminated silica was dispersed in a mixed solvent consisting of 100 mL of deionized water and 100 mL of anhydrous ethanol. Then, 5.0 g of sodium chloroacetate was added. Under vigorous stirring, the pH of the reaction system was maintained at 9 with 1 M sodium hydroxide solution, and the reaction was carried out in a water bath at 60 °C for 4 h. After the reaction was completed, the solid was collected by suction filtration, washed with deionized water until the filtrate was neutral, and finally dried under vacuum at 60 °C to obtain modified mesoporous nano-silica.
[0086] Weigh 10.0 g of sodium alginate and slowly add it to 90 mL of continuously stirred deionized water. Stir at room temperature for 6 hours until completely dissolved to obtain a sodium alginate solution. Separately weigh 2.0 g of polyvinyl alcohol and add it to 50 mL of 90°C deionized water. Stir vigorously in a 90°C water bath for 3 hours until completely dissolved to obtain a PVA solution, and then cool to 50°C. Mix the two solutions, then add 0.3 g of polyethylene glycol 400 and 0.3 g of modified mesoporous nano-silica. Mechanically stir at 350 rpm for 5 hours in a 50°C water bath. Finally, degas the mixture under a vacuum of -0.095 MPa for 60 minutes to obtain a homogeneous and transparent SA-PVA blend spinning solution.
[0087] Step 2: Dissolve 40.0g calcium chloride and 1.0g calcium gluconate in 1L of deionized water, stirring until completely dissolved. Place in a composite coagulation bath, maintaining a constant temperature of 40℃. Load the SA-PVA blend spinning solution into an injection pump, using a spinneret with an inner diameter of 0.12mm, and vertically inject the spinning solution into the coagulation bath at a constant rate of 6mL / h. The nascent fibers remain in the coagulation bath for 90s to solidify, during which time they are drawn through guide rollers at a speed of 3.5 m / min. Remove the solidified fibers, rinse thoroughly with deionized water, and absorb excess surface moisture with filter paper. Then, wrap the fibers in plastic wrap and freeze at -20℃ for 4 hours, followed by thawing at a constant temperature of 25℃ for 2 hours. Repeat this freeze-thaw cycle three times to obtain double-network hydrogel nascent fibers.
[0088] Step 3: Crush 100g of dried camellia flowers and pass them through a 40-mesh sieve. Add the powder to 1.5L of 60% (v / v) ethanol aqueous solution and perform ultrasonic-assisted extraction (ultrasonic power 300W) for 60min at 55℃. Filter the extract through a Buchner funnel, collect the filtrate, and rotary evaporate it under reduced pressure at 50℃ until no alcohol odor remains, obtaining crude camellia flower extract. Dissolve the crude extract in deionized water and load it onto a pretreated AB-8 macroporous adsorption resin column. Elute with water until the eluent is colorless, then elute with 50% (v / v) ethanol aqueous solution, collecting the eluent. Concentrate the eluent under reduced pressure at 50℃ and freeze-dry to obtain a brownish-yellow camellia flower extract.
[0089] Weigh 8.0 g of camellia extract and 3.0 g of zinc sulfate heptahydrate, dissolve them in 188 mL of deionized water, and stir until completely dissolved to obtain a treatment solution. Immerse the nascent double-network hydrogel fibers in this treatment solution at a bath ratio of 1:15, and treat them in a water bath shaker at 70 rpm for 50 min at 45°C. After treatment, remove the fibers and blot off surface droplets with filter paper to obtain a fiber intermediate loaded with camellia extract.
[0090] Step 4: Dissolve 1.0 g of gelatin in 20 mL of 50°C deionized water to obtain solution A; dissolve 0.5 g of gum arabic in 20 mL of 50°C deionized water to obtain solution B. Mix solution A with 1.0 g of camellia oil and homogenize at 8500 rpm for 3 min to form a primary emulsion. Add solution B to the primary emulsion with slow stirring, mix well, and adjust the pH of the system to 7.5 with 1% NaOH solution. Then, with continuous stirring, slowly lower the pH of the system to 4.2 with 10% acetic acid solution, and then transfer to an ice-water bath to cool to below 10°C. Add 0.1 g of genipin as a crosslinking agent and continue stirring to solidify for 3 h. After the reaction is complete, collect the microcapsules by filtration, wash three times with cold deionized water, and obtain camellia oil microcapsules.
[0091] Camellia oil microcapsules were dispersed in 20g of a 10% aqueous polyurethane (WPU) adhesive solution and ultrasonically dispersed for 2 minutes to form a homogeneous slurry. The fiber intermediate was then impregnated with this slurry, with the roll-off rate controlled at 85%, and then heat-treated in a 75℃ forced-air drying oven for 15 minutes to obtain hydrogel seaweed fibers containing camellia active ingredients.
[0092] Step 5: Open and comb the hydrogel seaweed fibers containing camellia flowers to make them fluffy single fibers. Then, use an air-jet web forming machine to lay the fibers into a surface density of 45 g / m². 2 A uniform fiber web is obtained. This fiber web is fed into a hydroentangling reinforcement device, where it is pierced by water flow through three hydroentangling heads under a hydroentangling pressure of 40 bar. Then, it is gently dried in an oven at 65°C for 10 minutes to obtain the mask base fabric.
[0093] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that polyvinyl alcohol is not added in step 1 of the preparation process of the seaweed fiber mask base cloth.
[0094] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that modified mesoporous nano silica is not added in step 1 of the preparation process of the seaweed fiber mask base fabric.
[0095] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that the seaweed fiber mask base fabric was not modified in step 1 of the preparation process.
[0096] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that step 3 is omitted in the preparation process of the seaweed fiber mask base cloth, that is, the fiber is not loaded with camellia extract.
[0097] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that step 4 is omitted in the preparation process of the seaweed fiber mask base cloth, that is, camellia oil microcapsules are not attached to the fiber.
[0098] Performance testing:
[0099] 1. Water Absorption Test: A 10cm × 10cm sample of the mask base fabric was placed in a 60℃ oven and dried to constant weight (mass recorded as m0). The sample was then completely immersed in 25℃ deionized water, left to stand for 30 minutes, and then removed. Excess surface moisture was gently absorbed with filter paper, and the sample was immediately weighed (mass recorded as m1). The water absorption rate was calculated using the formula: Water Absorption Rate = (m1 - m0) / m0 × 100%. Each test was repeated three times, and the average value was taken. The test results are shown in Table 1.
[0100] 2. Moisture retention test: The sample that has completed the water absorption test (mass denoted as m1) is placed in a constant temperature and humidity chamber at 37℃ and 50% relative humidity. After 4 hours, it is removed and weighed (mass denoted as m). t According to the formula, the moisture retention rate = (m t The result was calculated as (-m0) / m1×100%, and each test was repeated 3 times, with the average value taken. The test results are shown in Table 1.
[0101] 3. Moisture Evaporation Rate Test: Take a dry, constant-weight sample (mass m0), absorb water until saturated, and weigh it (mass m2). Immediately suspend it in an environment of 37℃ and wind speed of 0.5m / s (simulating facial application conditions). Weigh it every 30 minutes (mass recorded as m3) for 2 hours. Calculate the evaporation rate using the formula: Evaporation Rate = (m2 - m3) / (S × t) (where S is the sample area and t is time). Repeat each test 3 times and take the average value. The test results are shown in Table 1.
[0102] 4. Tensile Strength Test: Referring to GB / T 14344-2008 "Test Method for Tensile Properties of Short Chemical Fibers", a 20cm long sample with a linear density of 2.2 dtex was prepared from fibers in the mask base fabric. A universal testing machine was used, with a clamping distance of 10cm and a tensile speed of 10mm / min. The maximum tensile force (F) at break was measured. Tensile strength was calculated using the formula: Tensile Strength = F / Linear Density, in cN / dtex. Each test was repeated 5 times, and the average value was taken. The test results are shown in Table 1.
[0103] Table 1:
[0104] Sample Water absorption rate (%) Moisturizing rate (%) <![CDATA[Water evaporation rate g / (m 2 ·h)]]> Fracture strength (cN / dtex) Example 1 433.2 81.6 12.8 3.47 Example 2 427.5 80.7 13.9 3.36 Example 3 430.3 81.0 13.3 3.42 Example 4 435.6 82.3 12.1 3.51 Example 5 423.1 80.1 14.3 3.31 Comparative Example 1 289.5 55.6 18.8 2.16 Comparative Example 2 325.7 62.5 16.3 2.57 Comparative Example 3 335.8 65.7 15.7 2.73 Comparative Example 4 408.6 76.9 14.2 3.40 Comparative Example 5 410.5 68.4 14.9 3.45
[0105] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a hydrogel seaweed fiber mask base fabric containing camellia flowers, characterized in that, Includes the following steps: S1. Mix sodium alginate solution with polyvinyl alcohol solution, then add polyethylene glycol and mesoporous nano silica, and after mechanical stirring and vacuum degassing, obtain a uniform spinning solution. S2. The spinning solution is extruded into a composite coagulation bath composed of calcium chloride and calcium gluconate through a wet spinning device, and then subjected to ionic cross-linking solidification and stretching. After that, the solution is subjected to freezing and thawing cycle treatment to obtain nascent fibers. S3. Prepare a complexing solution containing camellia extract and zinc sulfate heptahydrate, immerse the nascent fibers in the solution and shake to obtain fiber intermediates; S4. Microcapsules were obtained by using gelatin and gum arabic as wall materials and camellia oil as core material, and then curing them with a cross-linking agent. Microcapsules were dispersed in an aqueous polyurethane adhesive solution to form a slurry. Fiber intermediates were then immersed in the slurry and subjected to padding and heat treatment to obtain hydrogel seaweed fibers containing camellia flowers. S5. The hydrogel seaweed fiber containing camellia is opened and combed, and then the fiber is laid into a uniform fiber web by mechanical stacking or air-laid web formation. The fiber web is then subjected to hydroentanglement reinforcement treatment to obtain the hydrogel seaweed fiber mask base fabric containing camellia.
2. The method for preparing a hydrogel seaweed fiber mask base fabric containing camellia flowers according to claim 1, characterized in that, In step S1, the mass ratio of sodium alginate to polyvinyl alcohol is 10:2 to 4.
3. The method for preparing a hydrogel seaweed fiber mask base fabric containing camellia flowers according to claim 1, characterized in that, The mesoporous nano-silica undergoes modification treatment, including the following steps: S11. Mesoporous nano-silica is dispersed in toluene. Under inert atmosphere and stirring conditions, (3-aminopropyl)triethoxysilane is added to the system, the reaction is heated, the solid product is separated, washed with organic solvent, and dried to obtain aminated silica. S12. Aminated silica is dispersed in a mixed solvent consisting of deionized water and anhydrous ethanol, and then sodium chloroacetate is added. Under vigorous stirring, the pH of the reaction system is maintained between 9 and 11 using an alkaline solution. The reaction is heated, the solid product is separated, and after washing and drying, modified mesoporous nano silica is obtained.
4. The method for preparing a hydrogel seaweed fiber mask base fabric containing camellia flowers according to claim 3, characterized in that, In step S11, the mass ratio of mesoporous nano-silica to (3-aminopropyl)triethoxysilane is 10:0.5-1.
0.
5. The method for preparing a hydrogel seaweed fiber mask base fabric containing camellia flowers according to claim 3, characterized in that, In step S12, the mass ratio of aminated silica to sodium chloroacetate is 10:5 to 8.
6. The method for preparing a hydrogel seaweed fiber mask base fabric containing camellia flowers according to claim 1, characterized in that, In step S2, the mass ratio of calcium chloride to calcium gluconate is 40:1 to 3.
7. The method for preparing a hydrogel seaweed fiber mask base fabric containing camellia flowers according to claim 1, characterized in that, In step S2, the preparation method of camellia extract includes the following steps: S21. Dry and pulverize the camellia flowers into camellia flower powder, mix the camellia flower powder with an ethanol aqueous solution, and extract with ultrasonic assistance under heating conditions to obtain an extract; S22. Filter the extract, collect the filtrate, heat and concentrate under reduced pressure to obtain crude camellia extract; S23. After dissolving the crude extract of camellia in water, it is purified by passing it through a macroporous adsorption resin column. First, impurities are removed by elution with water, and then elution is carried out with an ethanol aqueous solution. The eluent is collected. S24. After concentrating the eluent under reduced pressure under heating conditions, freeze-dry it to obtain camellia extract.
8. The method for preparing a hydrogel seaweed fiber mask base fabric containing camellia flowers according to claim 1, characterized in that, In step S3, the mass ratio of camellia extract to zinc sulfate heptahydrate is 8:3-5.
9. The method for preparing a hydrogel seaweed fiber mask base fabric containing camellia flowers according to claim 1, characterized in that, In step S4, the mass ratio of gelatin to gum arabic is 1:0.5 to 1.
10. A hydrogel seaweed fiber mask base fabric containing camellia flowers, characterized in that, It is prepared by the method described in any one of claims 1-9 above.
